(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Polymers are tools used in novel drug delivery system to modify the drug release of pharmaceutical dosage form. Polyox is hydrophilic polymer made of non-ionic homopolymer of ethylene oxide. Polyox is popular for its film forming, binding, lubricating, mucoadhesive, viscosity imparting property in pharmaceuticals. Polyox are available in various grades based on its molecular weight. Lower molecular weight Polyox are widely used for immediate drug release based on erosion properties of the polymer like quick dissolving film and high molecular weight Polyox are used to retard the drug release based on swelling and erosion properties of the polymer in controlled release, sustained release, extended release, buccal films, ocular inserts, ocular gels, osmotic tablets and so on. Polyox plays an important role in design of a novel drug delivery system for both highly and poorly soluble drug due to its multifunctional property. This review is detailed on Polyox its advantages, disadvantages, salient feature, mechanism, stability and application in pharmaceutical dosage form.